Acoustic metamaterial panel for both fluid passage and broadband soundproofing in the audible frequency range - Jung, Jae Woong; Kim, Jae Eun; Lee, Jin Woo (Applied Physics Letters, 2018)
We present the design, including an experimental demonstration, of an acoustic metamaterial panel aimed at reducing incoming broadband noise in the audible frequency range while allowing an incoming fluid to pass through the holes formed in the panel. The noise reduction performance of the proposed acoustic metamaterial panel is attributed to an array of annular cavities enclosing the fluid passage holes. The acoustic behavior of the acoustic metamaterial panel is theoretically analyzed by the transfer matrix method, and an equivalent acoustic impedance of each annular cavity is included with its effective length in the derived transfer matrix. The effective bulk modulus for the acoustic metamaterial panel is then extracted from the transmission and reflection coefficients by using the retrieval method. It is shown that the frequency range of the negative effective bulk modulus coincides with the stop band of the acoustic metamaterial panel. The underlying physical mechanism for the negative effective bulk modulus is attributed to the out-of-phase motion of vibrating particles in adjacent annular cavities. A calculated transmission coefficient curve of the acoustic metamaterial panel is shown to be in good agreement with the measured one. The findings presented in this work should be useful in the design of a holey soundproof panel.
Keywords: Acoustic metamaterial; Audible frequency range; Effective bulk modulus; Experimental demonstrations; Physical mechanism; Retrieval methods; Transmission and reflection coefficient; Transmission coefficients